2008
DOI: 10.1007/s10973-007-8869-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of thermally-damaged LX-17

Abstract: Thermal damage was applied to o C for several hours. The damaged LX-17 samples, after cooled down to room temperature, were characterized for their material properties (density, porosity, permeability, moduli), safety, and performance. Weight losses upon thermal exposure were insignificant (< 0.1% wt.). The damaged LX-17 samples expanded, resulting in a bulk density reduction of 4.3%. Subsequent detonation measurements (cylinder tests) were conducted on the thermally-damaged LX-17 samples. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Pre-and post-exposure measurements of the sample weight, volume, and porosity were performed according to published procedures [7] and are reported in Table 4. Methods for calculating the fraction of open and closed pores are described in the literature [26].…”
Section: Thermally Induced Damagementioning
confidence: 99%
“…Pre-and post-exposure measurements of the sample weight, volume, and porosity were performed according to published procedures [7] and are reported in Table 4. Methods for calculating the fraction of open and closed pores are described in the literature [26].…”
Section: Thermally Induced Damagementioning
confidence: 99%
“…It has been shown that the presence of porosity, cracks, and defects within energetic materials can have a significant effect on the detonation velocity of the energetic. Specifically, the introduction of small-scale (order � 1-10 μm pores and defects) can produce hot spots that increase sensitivity [28,29], while larger voids ( � 100's μm and larger) have been shown to reduce detonation velocity [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…15 The introduction of coupling agents has been proved to be an economical, rapid, and versatile way to obtain enhanced interfacial bonding properties. [24][25][26] However, the signicant inter-and intramolecular hydrogen bonding results in the very low surface energy and poor adhesive performance of TATB. 16 Because of the extraordinary stability under thermal, impact, or shock-initiation conditions, TATB is commonly used in PBXs.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The blending of TATB and uoropolymer, such as LX-17 (92.5% TATB and 7.5% Kel-F800 by weight) and PBX-9502 (95% TATB and 5% Kel-F800 by weight), provides an effective way to make full use of their respective advantages and has been widely investigated in the academic and industrial elds. [24][25][26] However, the signicant inter-and intramolecular hydrogen bonding results in the very low surface energy and poor adhesive performance of TATB. 27,28 In addition, low intermolecular cohesion force, weak interfacial bonding with gas, and very low surface tension of uoropolymer lead to very poor adhesion with other materials.…”
Section: Introductionmentioning
confidence: 99%